Global value chains participation to enhance export: Evidence from Indonesian apparel SMEs - Nugroho, Muhammad Ilham (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2022)
After recording remarkable growth and gaining more prominence within the domestic economy, Indonesian small and medium enterprises (SMEs) are now being pushed by the government to go beyond the domestic market. Indonesian government has introduced global value chains (GVCs) to SMEs to boost their export in the last recent years. Apparel SMEs normally can join GVCs through backward or forward participation. But in this case, the GVCs’ impact on apparel SMEs export remains sluggish because they are highly concentrated in forward participation. This research, therefore, provides empirical cases on how Indonesian apparel SMEs can engage in backward participation to raise their competitiveness in global market using the evidence of apparel SMEs. Utilizing three dimensions of GVCs analysis: governance, upgrading, and local policy network, this research finds that SMEs can easily engage in backward participation to obtain foreign inputs by using the internet. Moreover, the decision to venture into GVCs and global market is heavily influenced by e-commerce. Findings of this research can provide guidance for Indonesian policymakers about the importance of GVCs on SMEs’ export performance, creating a better environment for manufacturing and cross-border e-commerce that can be exploited by SMEs as the largest economic driver.JEL Classification F59; F63; L67